Pengaruh Strategi React dengan Media Pembelajaran Berbasis Prezi terhadap Kemampuan Komunikasi Matematis - Fany Aviola Vanka; Meyta Dwi Kurniasih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine whether or not there is an effect of using the REACT strategy with Prezi-based learning media on mathematical communication skills. This type of research is quantitative using a quasi-experimental research method. The population in this study were all seventh grade students at SMP Negeri 194 Jakarta for the 2020/2021 academic year. The sample used was 66 students from class 2 class. Sampling using simple random sampling technique. The research instrument is in the form of a description question. The results of the normality test showed that the experimental class data were normally distributed and the control class data were not normally distributed. Hypothesis testing using a non-parametric test, namely the Mann Whitney test with a significant level of 5%, the value z_table=z_0.5(1-0.05) =z_0.475=1.96; because the value of z_count = 5.40. So that in determining the test criteria, the acceptance of Ha is: z_hitung>z_table. The results of this study can be concluded that there is an effect of REACT strategy with Prezi-based learning media on students' mathematical communication skills. Keywords: REACT Strategy, Prezi Learning Media, Students’ Mathematical Communication